Implicit Talker Training Improves Comprehension of Auditory Speech in Noise - Kreitewolf, Jens; Mathias, Samuel R.; von Kriegstein, Katharina (Frontiers in Psychology, 2017)
Previous studies have shown that listeners are better able to understand speech when they are familiar with the talker’s voice. In most of these studies, talker familiarity was ensured by explicit voice training; that is, listeners learned to identify the familiar talkers. In the real world, however, the characteristics of familiar talkers are learned incidentally, through communication. The present study investigated whether speech comprehension benefits from implicit voice training; that is, through exposure to talkers’ voices without listeners explicitly trying to identify them. During four training sessions, listeners heard short sentences containing a single verb (e.g., “he writes”), spoken by one talker. The sentences were mixed with noise, and listeners identified the verb within each sentence while their speech-reception thresholds were measured. In a final test session, listeners performed the same task, but this time they heard different sentences spoken by the familiar talker and three unfamiliar talkers. Familiar and unfamiliar talkers were counterbalanced across listeners. Half of the listeners performed a test session in which the four talkers were presented in separate blocks (blocked paradigm). For the other half, talkers varied randomly from trial to trial (interleaved paradigm). The results showed that listeners had lower speech-reception thresholds when the speech was produced by the familiar talker than the unfamiliar talkers. The type of talker presentation (blocked vs interleaved) had no effect on this familiarity benefit. These findings suggest that listeners implicitly learn talker-specific information during a speech-comprehension task, and exploit this information to improve the comprehension of novel speech material from familiar talkers.